Effects of substrate stiffness on phosphorylation of endothelial nitric oxide synthase and nitric oxide bioavailability / Forough Ataollahi - Forough, Ataollahi (2015)
Blood vessels are exposed to mechanical loading (pulse) approximately 75 times per minute. Mechanical loading triggers nitric oxide (NO) production, which is an essential mediator in blood vessel tone regulation. However, disorders, such as aging and atherosclerosis, affect NO produced in each pulse because of blood vessel stiffness. The mechanisms involved in reducing NO production in stiff blood vessels are not fully understood, because the mechanical environment in blood vessels is a complex system consisting of shear stress, tensile loading, and pressure that each of those involves specific mechanisms. This study aims to determine the effect of substrate stiffness on endothelial NO synthase (eNOS) phosphorylation and NO production under tensile loading. Bovine aortic endothelial cells were isolated through incorporation of a new method in conventional enzymatic digestion, and were characterized by CD.31, Von Willbrand Factor, 1,1’-dioctadecyl-1,3,3,3’,3’-tetramethylindocarbocyanine perchlorate acetylated LDL, and angiogenesis behavior. Then, cells were seeded on the substrates with different stiffness. Substrates were prepared through mixing polydimethylsiloxane (PDMS) gel with 5 wt% and 10 wt% alumina (Al2O3), and were characterized by mechanical, structural, and morphological analysis. Approximately 10% of the strains with 1 Hz frequency were applied on the cells seeded on the substrates for 3 h. NO production was then measured in the culture medium, and the intensity of eNOS phosphorylated at Serin1177 was detected in cell lysate through enzyme-linked immunosorbent assay (ELISA) kits. The incorporation of filter paper in conventional enzymatic digestion enhanced the purity of isolated endothelial cells to approximately 90%. Membrane characterization showed that Al2O3 particles were distributed properly in the PDMS base and did not affect the surface roughness. Moreover, adding Al2O3 to the PDMS base increased membrane stiffness. The Young’s modulus of the membranes was 0.331, 0.592, and 1.076 MPa for pure PDMS, PDMS/5% Al2O3, and PDMS/10% Al2O3, respectively. The stretch loading results showed that 10% stretch of cells seeded on compliant substrates (pure PDMS) with 1 Hz frequency and 3 h duration enhanced the fleuroscnce intensity of p-eNOS at Serin1177 to 1.6 and increased NO bioavailability to 600 μg/ml. However, p-eNOS intensity was 1.07 and 1.06 in PDMS/5% Al2O3 and PDMS/10% Al2O3, respectively, which were significantly less than the pure PDMS. Moreover, NO concentration in response to tensile loading decreased three times in cells seeded on PDMS/5% Al2O3 compared with those in pure PDMS, and was undetectable in PDMS/10% Al2O3. This study presented the findings related to the phosphorylation of eNOS and NO production in response to tensile loading. In addition, this study showed that tensile loading elevated eNOS phosphorylation and NO production dependent on substrate stiffness. Keywords: bovine aortic endothelial cells, polydimethylsiloxan, alumina, stretch, endothelial nitric oxide synthase, nitric oxide.